The SNAP-tag technology revised: an effective chemo-enzymatic approach by using a universal azide-based substrate - Rosa Merlo; Diego Caprioglio; Michele Cillo; Anna Valenti; Rosanna Mattossovich; Castrese Morrone; Alberto Massarotti; Franca Rossi; Riccardo Miggiano; Antonio Leonardi; Alberto Minassi; Giuseppe Perugino (Taylor & Francis Group, 2021)
SNAP-tag® is a powerful technology for the labelling of protein/enzymes by using benzyl-guanine (BG) derivatives as substrates. Although commercially available or ad hoc produced, their synthesis and purification are necessary, increasing time and costs. To address this limitation, here we suggest a revision of this methodology, by performing a chemo-enzymatic approach, by using a BG-substrate containing an azide group appropriately distanced by a spacer from the benzyl ring. The SNAP-tag® and its relative thermostable version (SsOGT-H5) proved to be very active on this substrate. The stability of these tags upon enzymatic reaction makes possible the exposition to the solvent of the azide-moiety linked to the catalytic cysteine, compatible for the subsequent conjugation with DBCO-derivatives by azide-alkyne Huisgen cycloaddition. Our studies propose a strengthening and an improvement in terms of biotechnological applications for this self-labelling protein-tag.